The Solution for Narrow Land Agriculture to Obtain Profit in Deli Tua, Indonesia - Sitinjak, Wahyunita (Budapest International Research and Critics University, 2018)
Rural poverty is influenced by the level of education of the head of the family, mastery of the base of the land area, and natural conditions (agricultural land). Likewise, in this study of 'Analysis of the Factors Causing Poor Farmers' Revenues in Deli Tua District', it is assumed that farm household income is influenced by factors of education of the head of household, extent of land tenure, access to financial institutions, existence of alternative business and family dependents. The purpose of this thesis research is; (I) to find out whether the extent of land tenure, education level, number of family dependents, accessibility to financial institutions and the existence of business alternatives affect the income level of farmers, (2) to find out whether there is an influence of land area differences on income levels, (3) find out whether there is an influence of the differences in the status of own land and rent to income level, and (4) to find out the income distribution between farmers who control the 0.5 ha cultivated area and farmers who control the cultivated area greater than 0.5 ha. The research was conducted using descriptive method Primary data was collected by distributing 68 questionnaires in 6 (six) villages and villages in Deli Tua sub-district, Deli Serdang district, namely Deli Tua sub-district, Deli Tua Barat and Deli Tua Timur and Mekar Sari village, Kedai Durian and Suka Makmur.